Lipid profiles and fibrinogen levels in coronary heart disease and dyslipidemic patients in Dr. Sardjito Hospital Yogyakarta - Pramudji Hastuti Tasmini, Radityo PA, Ahmad Husain Asdi Tri Hartati, Abdul Salam M Sofro (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2011)
Epidemiological studies indicated that fibrinogen and dyslipidemia were important risk factors for cardiovasculardisease (CVD). For several populations in theworld, increase in cholesterol level and decrease in high-density lipoproteincholesterol (HDL-C) were risk factors for coronary heart disease (CHD). The role of elevated fibrinogen in thrombosissuggests that it may be the causal pathway for certain risk factors of CHD. The aim of this study is to determine therole of lipid profile and fibrinogen level as risk factors of coronary heart disease. Blood samples were obtained fromCHD patients, dyslipidemic patients, and controls after they had fasted. Lipid profiles and fibrinogen level of CHDand dyslipidemic patients were determined and compared with controls. There were 92 subjects in this study,consisted of 35 CHD patients, 31 dyslipidemic patients, and 26 controls. There were significant difference intriglyceride level between CHD and dyslipidemic patients, also between dyslipidemic patients and controls (p<0.05).Significant difference in level of cholesterol also existed between CHD patients and dyslipidemic patients, alsobetween CHD patients and controls (p<0.05). In dyslipidemic patients, decreased in HDL-C level was risk factorfor CHD. Meanwhile for controls, high level of cholesterol and LDL-C also low level of HDL-C were risk factor forCHD, but fibrinogen level was not risk factor for CHD. In conclusion, lipid profile was risk factor for CHD whereasfibrinogen level was not risk factor for CHD.Keywords: lipid profile – fibrinogen - coronary heart disease - dyslipidemia